2017
DOI: 10.1021/acs.cgd.6b01493
|View full text |Cite
|
Sign up to set email alerts
|

Sonosynthesis of Vaterite-Type Calcium Carbonate

Abstract: Metastable nanoparticles of vaterite were formed using a simple ultrasound technique. The effects of ultrasound amplitude and duration, as well as solution concentration, were investigated. The produced particles were characterized using standard X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), and scanning and transmission electron microscopies (SEM and TEM, respectively). As expected, the ultrasound synthesis process caused the particle size to be smaller than with conventional (magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 56 publications
1
22
0
1
Order By: Relevance
“…It can be seen that the only two diffraction peaks appear at 2θ = 29.4 • and at 2θ = 26.7 • , which are ascribed to the most intense (104) and (112) crystallographic faces of calcite and vaterite, respectively. The diffraction peaks for calcite and vaterite for crystallographic planes and 2θ degree are in agreement with both crystals designations as was recently published using the ultrasound technique [59]. In the case of the XRD spectrum of Chi-P sample ( Figure 8B), it shows a typical non-crystalline XRD curve, suggesting an amorphous nature of Chi-P biopolymer.…”
Section: Characterization Of Caco 3 Crystals Through Amperometry Ftisupporting
confidence: 88%
“…It can be seen that the only two diffraction peaks appear at 2θ = 29.4 • and at 2θ = 26.7 • , which are ascribed to the most intense (104) and (112) crystallographic faces of calcite and vaterite, respectively. The diffraction peaks for calcite and vaterite for crystallographic planes and 2θ degree are in agreement with both crystals designations as was recently published using the ultrasound technique [59]. In the case of the XRD spectrum of Chi-P sample ( Figure 8B), it shows a typical non-crystalline XRD curve, suggesting an amorphous nature of Chi-P biopolymer.…”
Section: Characterization Of Caco 3 Crystals Through Amperometry Ftisupporting
confidence: 88%
“…6 It has been well established that the different polymorphs of CaCO 3 synthesized in an aqueous solution possess different morphologies: rhombohedral phased calcite is usually found as cubic particles, orthorhombic aragonite usually found as needle-like particles, while vaterite has a hexagonal structure that normally leads to spherical particles, 7 the CaCO 3 morphology, size, crystal structure, density, color, brightness and other physicochemical properties of a material are strongly dependent on its preparation technology. Several techniques have been used to manufacture special morphologies, different polymorphs, controllable size, well dispersed CaCO 3 , such as carbonation, [8][9][10][11][12] solvo or hydrothermal synthesis 12,13 , microwave-assisted synthesis, [14][15][16][17] sonochemical synthesis, 18 double water-in-oil-in-water emulsion, 19 wet precipitation 20,21 and other special synthesis processes and methods. 22 Now, precipitation method is the most important method to prepare CaCO 3 , the relationship between precipitation conditions and morphology of CaCO 3 is the object of many experimental studies but it still is disputed, 23 it has been reported that synthetic factors including concentration of reactants, stirring speed, Ca 2+ : CO 3 2À ratio, aging time and adding mode may signicantly affect the formation of the polymorphs CaCO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In the spectra, all peaks could be indexed to vaterite (ICDD: #033-0268) or calcite (ICDD: #005-0586) polymorphs. In each sample, vaterite peaks at 24.92°, 26.99° and 32.78° corresponding to (110), (112) and (114) crystallographic planes, and/or calcite peaks at 29.40°, 35.90° and 39.50° corresponding to (104), (110) and (113) crystallographic planes were observed at varying intensities [25]. The variation of polymorph content in synthesized CaCO3 particles with respect to the EG concentration is calculated by Rietveld Refinement of XRD patterns given in Figure 1a.…”
Section: Resultsmentioning
confidence: 99%